The impact of Duolingo as a learning tool to improve English vocabulary for EFL learners - Nanin Putri; Tasfiyata Salsabila; Bendaoud Nadif; Nanin Putri; Tasfiyata Salsabila; Bendaoud Nadif (INTENS (International Journal of English Education and Linguistics), 2026)
The use of Duolingo as a mobile-assisted language learning tool has gained prominence for enhancing vocabulary acquisition among English as a Foreign Language (EFL) learners. Despite existing research on its short-term effectiveness, questions remain about its long-term impact and the cognitive mechanisms involved. This study investigates the role of Duolingo in improving vocabulary retention through a quantitative experimental design involving 60 EFL learners aged 16–22 years. Participants, selected through purposive sampling, engaged with Duolingo for at least one month. Data were analyzed using linear regression analysis and Pearson correlation analysis via SPSS to determine the tool’s efficacy. The findings reveal a statistically significant improvement in vocabulary retention, highlighting Duolingo's potential as a gamified, interactive, and accessible platform for self-paced learning. These results underscore its value in addressing gaps in traditional classroom methods, offering educators practical insights into integrating technology into curriculum design. This research contributes to the understanding of mobile-assisted tools, promoting their scalability for diverse educational context.